How can Au Gré Du Vin Increase Its Brand Awareness and Develop An Impactful Social Media Strategy? - Awaloedin, Nadira Alifanda; Archambault, Catherine; Hadiansyah, Fikri (Journal of Business and Management, 2021)
In the era of digitalization and with the occurrence of the pandemic, social media have become a crucial piece of a business marketing strategy as it eases companies to connect with their target customers, increase awareness, and boost their leads and sales. Due to the change of ownership and the impact of the pandemic, Au Gré Du Vin, a cellar specialist in natural and organic wines from Languedoc-Roussillon & Southwest in France, struggles to persistently stay relevant and show their unique selling proposition online specifically on Instagram, Facebook, and its official website. These three platforms have different objectives. Thus, must be utilised according to the features available and show alignment in aesthetic, content, and values to highlight brand identity and USP. Leading to a research question of “How can Au Gré Du Vin Increase Its Brand Awareness and Develop An Impactful Social Media Strategy?” as this research leverages a qualitative approach using both primary and secondary data collection processes.Keywords: Marketing, Social Media, Brand Awareness, Strategy, Wines, France.